Lithuania‘s relations with the West within the KGB Web - Burinskaitė, Kristina (Genocidas ir rezistencija, 2020)
The mechanisms for maintaining control of the Soviet territory and information, the so-called ‘Iron Curtain’, were very diverse (political, legal, coercive, agency networking) and were supported by certain institutions. The aim will be to describe the role played by this institution in controlling relations with the West during personal, tourist trips both domestically and abroad, and on official missions.The Soviet system sought to classify information that could damage the image of the Soviet-as-advanced system and reveal strategically important (political, economic, military, social) information that the West could supposedly use against it. Therefore, it was important that sensitive information would not be known by persons staying in Lithuania and that it would not be disseminated by Lithuanians going abroad. In view of this, the procedure of movement of foreigners on the territory of Lithuania (what cities and sites were allowed to be visited, with which people communication was allowed) and the rules of the presence of Lithuanians abroad (tourists, missions, etc.) were drawn up. To achieve these objectives, the KGB used its own methods: operational-technical tools, agency network and various instructions.According to the KGB, the greatest threat from arrivals was potential espionage, so all attention was paid to preventing possible espionage. The KGB, using all its means, had been monitoring where foreigners were going, who they were communicating with and how they behaved. Diplomats and journalists arriving in the country were particularly scrutinized. They were almost automatically equated with special service agents, as were scientists and industry professionals. The control of the movement and communication of foreigners with the local population was to be ensured by agents accompanying them, trusted persons (guides, interpreters, bus drivers, restaurant and hotel workers), disguised workers working incognito, and secret operational technical devices.The KGB’s intelligence agency activities were no less important than the fight against the regime’s internal enemies. It included not only espionage, but also propaganda-disinformation campaigns in the West. The agents were the eyes of the KGB and the perpetrators of their plans abroad. It was important for them to protect Soviet citizens from Western temptations, recruitment and escape, as this could damage the image of the Soviet system and allow for the flow of important information to the West. However, the facts of the violation of the order of the presence of tourists in Lithuania, and the cases of escape of Soviet citizens, recorded by the KGB, show that even the KGB did not have such opportunities to follow each tourist, prevent espionage and reveal the potential intentions of departing persons. It was even more difficult to control the departing Lithuanians, as evidenced by the escapes to the West, even by KGB agents.
Keywords: KGB; tourism; agents; emigree; economy; West